Islamism and Islam - Bassam Tibi (Yale University Press, 2012)
The fi rst message of this book is that there is a distinction between the faith of Islam and the religionized politics of Islamism, which employs religious symbols for po liti cal ends. Many will deny this distinction, including most prominent Islamists themselves. There is no doubt that many Islamists hold the sincere conviction that their Islamism is the true Islam. In fact, however, Islamism emanates from a po liti cal interpretation of Islam: it is based not on the religious faith of Islam but on an ideological use of religion within the po liti cal realm. Islamism and Islam are thus different entities, not to be confused with each other, and in this book I aim to explain this difference. In the fi eld of Islamic studies, the difference between Islamism and Islam is largely ignored or even dismissed. But for reasons that will become clear, the distinction is crucial to any belief that Muslims can live in peace with non- Muslims. The religious faith of Islam is not an obstacle to peace or a threat to the non- Muslim other. Islamism, on the other hand, creates deep civilizational rifts between Muslims and non- Muslims. It not only labels â€œJews and crusadersâ€ as the enemy but also targets other non- Muslims: Hindus in Kashmir and Malaysia, Buddhists and Confucians in China and Southeast Asia, people of African animist religions in Sudan. Islamism classifi es all non- Muslim people as kuffarâ€” infi delsâ€”and thus â€œenemies of Islam.â€ Liberal Muslims are not immune either. As well as contributing to polarization between Muslims and the non- Muslim other, Islamism also generates ferocious infi ghting within the community of Islam. In its jihad against â€œenemies of Islam,â€ Islamism seeks to excommunicate even liberal Muslims from the ummaâ€” the worldwide Muslim community. To protect themselves against criticism, Islamists have invented the formula of â€œIslamophobiaâ€ to defame their critics. In contrast, in this book I combine respect for the faith of Islam with a staunch critique of Islamism. It is no contradiction to defend Islam against prejudice and to criticize Islamism.